2017
DOI: 10.1016/j.jmu.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Ultrasound Scoring System for Preoperative Prediction of Difficult Laparoscopic Cholecystectomy

Abstract: PurposeLaparoscopic cholecystectomy (LC) has become the treatment of choice for cholelithiasis. Still some patients required conversion to open cholecystectomy (OC). Our aim was to develop a standardized Ultrasound based scoring system for preoperative prediction of difficult LC.Methods and materialsUltrasound findings of 300 patients who underwent LC were reviewed retrospectively. Four parameters (time taken, biliary leakage, duct or arterial injury, and conversion) were analyzed to classify LC as easy or dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 16 publications
3
48
2
1
Order By: Relevance
“…In 2017, Siddiqui et al study found that there was no any statistical significance between difficulty during LC and the presence of pericholecystic collection, multiple stones or enlarged liver (20) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In 2017, Siddiqui et al study found that there was no any statistical significance between difficulty during LC and the presence of pericholecystic collection, multiple stones or enlarged liver (20) .…”
Section: Discussionmentioning
confidence: 98%
“…In 2017, Siddiqui et al study found that patients with an impacted stone had higher incidence of operative difficulty and the association between the two was statistically significant (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El US está limitado en lo que se refiere a la identificación de variantes del árbol biliar. Otras modalidades de imagen, tales como la colangiopancreatogra-fía por resonancia magnética (CPRM) y la Colangiopancreatografía Retrograda Endoscópica (CPRE) pueden ser útiles en el abordaje preoperatorio y mejorar los resultados [32][33][34][35] .…”
Section: Fuente De Datos Y Revisión Del Tópicounclassified
“…Demographic, laboratory, and intraoperative factors that predict or contribute to conversion have been previously evaluated, but no consensus has emerged (37). In addition, some studies have conducted and published studies on radiologic factors contributing to conversion, but most studies have used ultrasound (US) findings (810). Despite the fact that contrast-enhanced computed tomography (CECT) is commonly performed in the emergency room for patients with acute abdominal pain and tenderness during the initial work-up, only a few studies on whether CT findings were associated with conversion to open cholecystectomy have been reported (11).…”
Section: Introductionmentioning
confidence: 99%